Existence and Preservation Strategy of the To Wani Tolotang Hindu Indigenous Community in Parepare - Abidin, Abdi Dermawan; Manda, Darman; Ahmadin, Ahmadin; Nasuhan, Najamuddin (Universitas of Muhammadiyah Makassar, 2025)
The To Wani Tolotang Hindu Indigenous Community is facing major challenges due to modernization, urbanization, and social changes that have the potential to threaten the survival of their culture and religion. In this study, there are limited data because traditional leaders only exist in Sidrap, precisely in Amparita. This study aims to analyze the sustainability factors of the community in Bakukiki District, Parepare City. Based on this goal, it is in accordance with the results of the research where in the research the existence of the indigenous community is still maintained until now, as evidenced by various strategies that have been applied in the lives of the people in the community. With a phenomenological approach, data were collected through observation, interviews, and documents/documentation of 16 selected informants using purposive sampling. The data analysis techniques in this study use data reduction, data presentation, and conclusion drawn. This study contributes so that the next research can provide a better picture of the form of existence of an indigenous community in Indonesia. The results of the research show that the sustainability of the community is supported by strong beliefs, the implementation of traditional ceremonies, and cultural identities that continue to be maintained. This research recommends further collaboration for community preservation